Association of sedentary behavior and metabolic syndrome - Lemes, I. R. [UNESP] (2019)
Objectives: To examine the association of sedentary behavior (SB) with metabolic syndrome (MetS) in adults, as well as to identify the impact of physical inactivity and economic condition on such association. Study design: This is a cross-sectional study. Methods: This study was conducted in the city of Bauru, São Paulo State, Brazil (n = 970). Television (TV) viewing and physical activity (PA) were assessed by questionnaire. MetS was assessed via medical records. Descriptive statistics and binary logistic regression were used in data analyses. Results: Participants with moderate TV viewing were associated with MetS when compared with low TV viewing group, even after adjustments for age, sex, economic status, smoking, and PA (odds ratio [OR] = 1.49 [95% confidence interval CI: 1.01–2.20]). The fully adjusted model showed an association between high exposure to TV viewing with MetS (OR = 1.77 [95%CI: 1.11–2.82]). The combination of physical inactivity and high TV viewing boosted the likelihood of having MetS (OR = 1.89 [95%CI: 1.08–3.29]). Conclusion: The results of the present study suggest that moderate and high TV viewing time is associated with the presence of MetS, mainly in insufficiently active adults and those living in lower economic condition.